Technologic appliance and performance concerns in wheelchair racing - Helping Paralympic athletes to excel - Forte, P.; Barbosa, T. M.; Marinho, D. A. (New Perspectives in Fluid Dynamics, 2015)
Numerical simulations have provided useful evidence in helping several sportsmen to excel in their field. This methodology aims to have a deeper understanding on the influence of equipment and sports techniques on sports performance. In wheelchair racing, technology was used without considering specific sport (some of the Paralympic sports used the same technology of their Olympic counterparts). It has induced unique changes in prosthetic and wheelchair devices. Eventually, technology has become an essential part of Paralympic sports, wheelchair-racing being one of the most popular events. Numerical simulations can help us gather evidence on the effects of drag force acting upon the athlete-chair system.Different types of wheelchairs are designed for racing (track and road races), net, and invasion sports. One of the various strategies to enhance performance is to minimize the aerodynamic drag of the frame, tires, helmet, sports outfit, and body posture.Numerical simulations can be used to predict the fluid dynamics.The goal of this chapter is to review the state-of-the-art numerical simulations and suggest further studies in wheelchair racing. The chapter will include sections covering: (i) main determinants in wheelchair racing; (ii) the effect of aerodynamic force in in wheelchair racing performance; (iii) analytical models, experimental testing, and numerical simulations in wheelchair racing; and (iv) numerical simulations on equipment and techniques.